Health and pollution in a vertically differentiated duopoly - Stefano Quarta; Skerdilajda Zanaj (Economics and Econometrics Research Institute (EERI), 2019)
In this paper, we analyze a vertically differentiated mixed duopoly in medical care services. Pollution is the source of illness. The government has a dual role. It decides how much to invest to reduce the pollution level and it may participate in the health market running a public hospital. We find that the presence of the public provider increases the average quality of the service in the market and it reduces the rate of mortality. Furthermore, when the public hospital offers services with the highest quality, then this has positive spillovers on the quality offered by the private provider. Despite these positive welfare improving features, the mixed duopoly in medical care goes along with the highest level of pollution. In the presence of an increasing concern about the relationship between pollution and health, understanding the role of public intervention appears crucial.
Keywords: L13; H42; H44; I11; 330; Pollution; health; public provider; mixed duopoly